The effect of heat treatment applied to cereals used in dog foods on gelatinization and digestibility of starch - Fatma İnal; Abdullah Özbilgin; Mustafa Selçuk Alataş; Oğuzhan Kahraman; Emel Gürbüz (Eurasian Journal of Veterinary Sciences)
Aim: It is to determine the effects of soaking, cooking in water, extrusion applied to the cereals used in dog foods on the gelatinization and digestibility of starch. Materials and Methods: Barley, wheat, corn, rice, sorghum and oat were used. Milled grains were soaked with boiling water, cooked with water for 10 min and 20 min, and extruded. The heat treated cereals were dried and ground. Dry matter, starch, gelatinized starch and in vitro starch digestibility analyzes were performed in all samples. Results: The amount of starch in the heat treated cereals decreased. It was found that the richest cereal in terms of starch is rice and the poorest one is oat. The starch damage was determined as 4.64% in raw cereals, 30.99-31.83% in cereals cooked with water and 31.59% in extruded cereals. Heat treatments increased starch gelatinization by 581%. The highest gelatinization occurred in the oat. In vitro starch digestibility was found 14.62 in raw grains, 55.46 after cooking for 10 min and 72.47 mg maltose/mg starch after extrusion (P <0.05). Heat treatments increased starch digestibility by 308%. The highest starch digestibility occurs in the oat and the lowest in rice. There was not any gelatinized starch ratio difference between the cooking and extrusion, but starch digestibility was found higher after the extrusion (P<0.05). Soaking with boiled water was not effective in increasing starch gelatinization and digestibility. Conclusion: In similar studies with cereals, it may be advisable to determine amylopectin, amylose, resistant starch contents, and feeding experiments.